A NEEDS ANALYSIS OF ENGLISH FOR SPECIFIC PURPOSES (ESP) FOR INFORMATION TECHNOLOGY STUDENTS: A LINGUISTIC AND PEDAGOGICAL PERSPECTIVE - Ika Susanti; Sartika Hijriati; Yusuf Al Arief; Dian Karina (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyse the English language needs of Information Technology (IT) students from both linguistic and pedagogical perspectives. The research seeks to identify the students’ specific language requirements and the implications for curriculum design in English for Specific Purposes (ESP). Using a mixed-method approach, data were collected from 80 students of the Information Systems and Technology Program at ITB Semarang through questionnaires, interviews, and document analysis. The findings revealed that reading and writing are the most essential skills for IT students, especially in understanding technical documentation and producing project reports. Students also expressed a strong need for vocabulary enrichment, authentic materials, and digital-based communication practices. The pedagogical implications suggest that ESP instruction should integrate task-based and project-oriented learning, align materials with professional contexts, and emphasize communicative competence in technology-related discourse. Keywords: English for Specific Purposes, Needs Analysis, Information Technology